The Implementation of the Collaborative Learning Approach in Teaching Speaking: A Case Study of an Indonesian EFL Classroom - Haidir, Asia Masita; Dollah, Syarifuddin; Basri, Muhammad; Sakkir, Geminastiti (Universitas Cokroaminoto Palopo, 2025)
This study aims to examine the implementation of the collaborative learning approach in teaching speaking in English as a foreign language (EFL) classrooms in Indonesia. Adopting a qualitative case study approach, the research involved two English teachers from a non-formal English course institution. Data were gathered through in-depth interviews and classroom observations to explore how teachers applied the collaborative learning approach and the challenges they encountered.The findings reveal that this approach enhances students' confidence in speaking English, encourages more active participation in discussions, and improves their comprehension of the material. Teachers observed that students working in small groups tend to absorb language structures more effectively and develop greater fluency compared to those engaged in individual learning. However, several challenges arise, including variations in students’ proficiency levels, unequal contributions within groups, and difficulties in managing classroom dynamics. To address these challenges, teachers implement strategies such as assigning specific roles within groups and establishing structured speaking guidelines. Moreover, this approach positively impacts students' emotional engagement by boosting their motivation and fostering a more interactive learning environment. In conclusion, collaborative learning has been proven to effectively enhance students' speaking skills. However, its successful implementation requires well-planned strategies to ensure active participation from all students